When “altering brain function” becomes “mind control” - Koivuniemi, Andrew; Otto, Kevin (Frontiers in Systems Neuroscience, 2014)
Functional neurosurgery has seen a resurgence of interest in surgical treatments for psychiatric illness. Deep brain stimulation (DBS) technology is the preferred tool in the current wave of clinical experiments because it allows clinicians to directly alter the functions of targeted brain regions, in a reversible manner, with the intent of correcting diseases of the mind, such as depression, addiction, anorexia nervosa, dementia, and obsessive compulsive disorder. These promising treatments raise a critical philosophical and humanitarian question. “Under what conditions does ‘altering brain function’ qualify as ‘mind control’?” In order to answer this question one needs a definition of mind control. To this end, we reviewed the relevant philosophical, ethical, and neurosurgical literature in order to create a set of criteria for what constitutes mind control in the context of DBS. We also outline clinical implications of these criteria. Finally, we demonstrate the relevance of the proposed criteria by focusing especially on serendipitous treatments involving DBS, i.e., cases in which an unintended therapeutic benefit occurred. These cases highlight the importance of gaining the consent of the subject for the new therapy in order to avoid committing an act of mind control.